Face perception in its neurobiological and social context - Souza, Wânia C. de (2008)
Significant advances in the understanding of processes involved in face perception have been achieved. This study aims to review the literature of face perception in neurobiological and social contexts. The review focused on the mechanisms of mediation of face perception by neural substrates, and discussed some of the social signals provided by faces. We showed that psychological, neurophysiological and neuroimaging studies have demonstrated that a dedicated neural system for face perception exists in primates, which includes the fusiform face area (FFA), anterior superior temporal sulcus (STS) and anterior inferior temporal gyrus (ITG). But it remains to be understood how the integration of face perception occurs in the neurobiological context and in the social context.